Optimization design based approach for the determination and minimization of the displacement under tensile load in hybrid composite joint (Fracture and Structural Integrity, 2020)
CComposite materials are most often used for lengthier and thin structures susceptible to buckle. The optimization is often carried out taking into consideration the resistance to buckling and tensile loads for minimum displacement i.e maximization of the tensile load for composite assembly joint. It well known that nowadays that composite material in structural mechanics is widely used in many industrial sectors such as in aerospace and aeronautic, automobile, marine  industries as well as in and civil engineering. Composite materials are attractive due to their advantages and performance i.e: lighter weights, high resistance to thermal and mechanical loads, resistance to corrosion and wear.In this paper an investigation is focused on the problem of hybrid assembly joint (bolted –bonded) composite structures. The aim is the optimization of the main influencing parameters.A bonded assembly has only one advantage which is its lightness; on the other hand bolted assembly has the inconvenient of increasing the weight of the structure and stress concentrators. In practice certain structural designs require the use of hybrid assembly for safety and reliability. The objective of this study is to optimize the influencing factors using both Genetic Algorithm and design of experiments for high mechanical performance of hybrid composite assembly.
Keywords: hybrid composite joint; genetic algorithm; composite structure; adhesive; optimization